A quantitative method to detect fucoidan in human plasma using a novel antibody - Irhimeh M.R. (2014)
We have developed an antibody-based method to assess plasma uptake of a proprietary Undarian-derived fucoidan galactofucan sulfate (GFS™) after oral ingestion by human volunteers. Fucoidans have high-molecular-weights but exert biological effects in experimental animals after oral intake. By using a novel antibody raised against sulfated polysaccharides, we carried out a competitive ELISA to quantitate GFS in plasma samples from healthy volunteers who ingested 3 g/day of whole Undaria containing 10% GFS fucoidan, purified 75% GFS fucoidan, or 3 g of a nonsulfated placebo polysaccharide over 12 days. Increased reactivity to the novel antibody, as measured against preingestion levels, was detected at all time points. Assuming the measured material to be intact GFS, the concentration detected (median) was 4.002 and 12.989 mg/l when 3 g of 10% or 75% pure fucoidan was ingested orally over a period of 12 days, respectively. High-molecular-weight fucoidan can be detected in plasma using an ELISA competitive assay based on a novel antibody to sulfated polysaccharides. © 2005 Prous Science. All rights reserved.